Can Insurance Market Competition Coexist With Provider Price Regulation? Evidence From Medicare Advantage - Robert A. Berenson MD; Judith Feder PhD; Laura Skopec MS (SAGE Publishing, 2019)
Proposals to contain health care costs often draw from 1 of 2 primary policy approaches-price regulation or market competition. These approaches are often viewed as in conflict, even though some health economists have long argued that they may be compatible, and desirable, given the unique characteristics of health care markets. Medicare Advantage (MA) markets provide a real-world example supporting the view that provider price regulation and insurance market competition can be complementary.